Research on the Architecture of Cold Chain Logistics Multimedia Monitoring and Tracking Service Platform Based on Fuzzy Sorting and Heuristic Algorithm. (14th September 2021) - Zhang, Qi
Abstract : With the continuous development of social economy, the logistics system has been continuously improved. In addition to traditional domestic postal transportation and car consignment, emerging logistics methods such as SF Express and Yunda have also emerged. Aiming at the features such as fragility of fruits and vegetables and high storage requirements, in this paper, a cold chain logistics multimedia monitoring and tracking service platform is built in an attempt to monitor the preservation environment and safety status of agricultural products relying on fuzzy sorting and heuristic algorithms, trace agricultural products with labels, and design the direction of the key data. The practice results show that the system is effective.